Pengaruh Akses Internet, E-commerce dan Belanja Teknologi Informasi terhadap Pertumbuhan Ekonomi Di Indonesia - Yesti Sepriyani; Ariusni (Universitas Negeri Padang, 2026)
This study motivated by the importance of digital transformation in promoting economic growth in Indonesia and the limited empirical studies that simultaneously examine the effects of internet access, e-commerce and information technology expenditure at the provincial level. The objective of this study is to analyze the impact of internet access, e-commerce and information technology expenditure on economic growth in Indonesia. This research uses secondary data form Statistics Indonesia (BPS) covering 34 provinces during the period 2019-2023 and applies panel data regression with the Random Effect Model as the selected model. The results show that internet access has a positive and significant effect on economic growth, while e-commerce has a positive and significant effect with a one period lag. Meanwhile, information technology expenditure has a negative and significant effect on economic growth. Simultaneously, all independent variables significantly influence economic growth in Indonesia. These findings indicate that digital connectivity and e-commerce utilization contribute to economic performance, yet the effectiveness of information technology expenditure needs improvement. Therefore, the government is advised to enhance digital infrastructure, strengthen digital literacy and improve the efficiency and governance of information technology spending to support inclusive and sustainable economic growth.